Current Perspectives in the MRI Diagnosis of Multiple Sclerosis: The 2016 Revised MRI Criteria - Bryukhov, V. V.; Krotenkova, I. A.; Morozova, S. N.; Krotenkova, M. V. (Neuroscience and behavioral physiology, 2018)
MRI scanning is the main widely used diagnostic method for multiple sclerosis (MS). This article discusses the current state of the question of the effectiveness of using brain and spinal cord MRI scans in the diagnosis of patients with suspected MS. Particular attention is paid to the McDonald MRI and MAGNIMS criteria as revised in 2010 and 2016 for both remitting MS and primary progressive MS. The data presented here allow radiologists and neurologists to optimize the use of MRI scans in clinical practice for the diagnosis of MS.